[μ-Bis(diphenylarsino)methane-1:2κ(2) As:As′]nonacarbonyl-1κ(3) C,2κ(3) C,3κ(3) C-[triphenylstibine-3κSb]-triangulo-triruthenium(0) - Shawkataly, Omar bin (International Union of Crystallography, 2009)
In the title triangulo-triruthenium compound, [Ru(3)(C(25)H(22)As(2))(C(18)H(15)Sb)(CO)(9)], the bis(diphenylarsino)methane ligand bridges an Ru—Ru bond and the monodentate stibine ligand bonds to the third Ru atom. Both the stibine and arsine ligands are equatorial with respect to the Ru(3) triangle. Additionally, each Ru atom carries one equatorial and two axial terminal carbonyl ligands. The three stibine-substituted phenyl rings make dihedral angles of 84.3 (3), 80.4 (3) and 70.5 (3)° with each other. The dihedral angles between the two phenyl rings are 85.9 (3) and 75.2 (3)° for the two diphenylarsine groups. In the crystal packing, molecules are linked into chains down the c axis via intermolecular C—H⋯O hydrogen bonds. Weak intermolecular C—H⋯π interactions further stabilize the crystal structure.